2017
DOI: 10.18805/lr.v0iof.9104
|View full text |Cite
|
Sign up to set email alerts
|

Variability, character association and path coefficient analysis of green pod yield and its related traits in pea (Pisum sativum L.)

Abstract: Genetic variability, character association and path coefficient studies were carried out for yield and yield contributing characters for twenty-four diverse genotype of pea. The results revealed a wide range of phenotypic variation, along with high heritability in pea. Highest pod yield per plant was recorded in VRP-229 followed by VRP-372 and VRP-305. The characters namely, plant height and weight of seeds per pod showed high magnitude, while number of pods per plant, number of branches per plant and pod yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 2 publications
(2 reference statements)
8
10
0
Order By: Relevance
“…Number of primary branches per plant (0.464) showed significant and positive correlation with pod yield per plant at genotypic level suggesting that direct selection for this trait should be practiced to develop high yielding genotypes. Similar observations were also reported by Pal and Singh (2012), Gautam et al, (2017) and Khan et al, (2017). Days to first picking (-0.641, -0.526) exhibited significant negative correlation with pod yield per plant both at genotypic and phenotypic levels.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Number of primary branches per plant (0.464) showed significant and positive correlation with pod yield per plant at genotypic level suggesting that direct selection for this trait should be practiced to develop high yielding genotypes. Similar observations were also reported by Pal and Singh (2012), Gautam et al, (2017) and Khan et al, (2017). Days to first picking (-0.641, -0.526) exhibited significant negative correlation with pod yield per plant both at genotypic and phenotypic levels.…”
Section: Resultssupporting
confidence: 90%
“…The results of path analysis revealed that days to 50 per cent flowering (0.493) had maximum positive direct effect on pod yield per plant followed by number of seeds per pod (0.394), number of pods per plant (0.260), shelling percentage (0.113), plant height (0.052) and total soluble solids (0.035) at the phenotypic level and days to 50 per cent flowering (1.460) followed by number of pods per plant (0.258), shelling percentage (0.135) and number of primary branches per plant (0.009) at genotypic level (Table 4). Similar findings have already been reported for number of pods per plant by Gautam et al, (2017), Sharma et al, (2009), Kumar et al, (2014 and Bijalwan et al, (2018). Sharma et al, (2011) also reported positive direct effect of shelling percentage on pod yield per plant.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Pod weight is another important yield component and needs due consideration while making selection for yield (GAUTAM et al, 2017). All the genotypes differ significantly for pod weight.…”
Section: Pod Weight (G)mentioning
confidence: 99%